Pengaruh Pembiasaan Menghafal Al Qur'an Surah Pendek Terhadap Karakter Siswa Kelas 5 di MI Takhasus Prapagkidul, Pituruh, Purworejo - Siti Mar’atul Badriya; Aniesatun Nurul Aliefah (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This research uses a quantitative approach where the respondents are students in classes 5A, 5B, 5C and 5D. Data collection techniques use questionnaires and documentation. The data analysis technique for this research uses instrument tests consisting of validity and reliability tests, classical assumption tests consisting of normality and linearity tests and hypothesis tests. Based on the research results, it can be concluded that: (1) students' habit of memorizing the Al Qur'an has an influence on the discipline character at MI Takhasus Prapagkidul. This is based on the results of the hypothesis test which shows that the sig. of 0.000 where the value is <0.005, so that it meets the criteria if Ha is accepted. Ha'adlah reads "There is an influence of memorizing the Qur'an on the character of discipline at MI Takhasus". (2) The magnitude of the influence of memorizing the Qur'an on the discipline character of students at MI Takhasus Prapagkidul is 53%. This can be seen from the correlation test table, the correlation coefficient value is 0.536. This value shows that the effect of memorizing the Qur'an on the discipline character of grade 5 students at MI Takhasus Prapagkidul is 53%, while the remaining 47% shows other factors not included in this research.